Understanding regime support in new and old democracies: the role of performance and democratic experience - Luis A. Camacho (Deutsches Institut für Entwicklungspolitik (DIE), 2014)
This paper develops a comprehensive theory of support for democracy. Building on instrumental and culturalist approaches, the theory argues that experience with democracy conditions the extent to which economic and political performance inform support. Specifically, it argues that the extent to which economic performance informs support should decline as a democracy grows older, while the opposite should be true about political performance. These arguments are evaluated using multilevel models to analyse cross-national survey data for 21 Latin American countries. The evidence indicates that both economic and political performance inform support for democracy and that the extent to which economic performance informs support declines as a democracy grows older. Although the importance of political performance does not seem to be conditioned by democratic experience, its importance in relation to economic performance does increase as a democracy matures. The evidence also indicates that experience with democracy, and not level of economic development, is what conditions the importance of economic performance. Altogether, these results suggest that support for democracy and a civic culture that values the political goods that democracy can deliver are more likely to be a consequence of, rather than a prerequisite for, the survival and eventual consolidation of democracy.
Keywords: 330; Governance; Demokratie und Autokratie